In vitro Determination of Fungicide Inhibitory Concentration for Phakopsora pachyrhizi isolates - Moura,Bianca (2016)
ABSTRACT In vitro assays were preformed to obtain the IC50 of eight fungicides against Phakopsora pachyrhizi isolates from Passo Fundo, RS, Ponta Grossa, PR, and Primavera do Leste, MT. Different concentrations of the fungicides were added to Petri dishes containing soybean leaf extract agar medium. One milliliter of P. pachyrhizi uredospore suspension at the concentration of 3.0 x 104 uredospores/mL was added to each dish for subsequent viability quantification. Only pyraclostrobin and the mixture trifloxystrobin + prothioconazole showed IC50 values inferior to 1.0 mg/L for all tested isolates, demonstrating high fungitoxicity. There was not loss of sensitivity to any of the tested fungicides.